From conformity to loss of control: psychological mechanisms in Suárez’s biting incidents and the development of the SDA model - Zhang, Zhao; Yu, Shaoran (Frontiers in Psychology, 2025)
Current studies on Luis Suárez’s three biting incidents in football reveal considerable shortcomings: an emphasis on discrete occurrences, disregard for dynamic psychological processes, and dependence on initial trait attribution. These deficiencies hinder the elucidations of recurrent unauthorised aggression by non-habitual aggressors in high-pressure situations. This research fills this need through case analysis and theoretical synthesis. Using biting occurrences as case studies, it amalgamates the self-control model and reversal theory to develop the stress-depletion-aggression model (SDA). The model outlines a three-stage hostility trajectory: (1) Internal and external stressors systematically diminish self-control resources through physiological and cognitive mechanisms; (2) Continuous depletion undermines inhibitory control and alters motivational priorities; (3) A transition in meta-motivational states (from conformist to negativistic + telic/mastery + telic) incites unsanctioned aggression. The findings indicate that the SDA model accomplishes multilevel integration of physiological, neurocognitive, and motivational factors; recognises ego depletion as the primary mediator between stress and motivational transitions; and improves predictive capability for unsanctioned aggression beyond conventional theories. The study indicates that unsanctioned aggression arises from the interactive effects of stress accumulation, resource depletion, and significant motivational-state shifts, establishing a scientific foundation for anticipating athlete hostility, formulating remedies, and optimising competition regulations. The proposed SDA model represents a novel theoretical integration, systematically combining the physiological-cognitive mechanisms of self-control resource depletion with the dynamic reversals of meta-motivational states, thereby providing a multi-level, testable framework for understanding and predicting sudden, unsanctioned aggression by non-habitual aggressors under high pressure.